Abolishing school fees in Africa : lessons from Ethiopia, Ghana, Kenya, Malawi and Mozambique. (Development practice in education., 2009)
Progress in literacy and learning, especially through universal primary education, has done more to advance human conditions than perhaps any other policy. Our generation has the possibility of becoming the first generation ever to offer all children access to good quality basic education. But it will only happen if we have the political commitment -- at the country as well as at the international level -- to give priority to achieve this first in human history. And it will only happen if also those who cannot afford to pay school fees can benefit from a complete cycle of good quality primary.